PENGARUH PERAN PROFESIONALITAS GURU PENDIDIKAN AGAMA ISLAM TERHADAP HASIL BELAJAR SISWA SMP MUHAMMADIYAH 1 TUBAN TAHUN PELAJARAN 2023/2024 - Ahmad Qoyyis Khikmawan dan Maftuhah (Jurnal Mahasiswa Pendidikan, 2024)
Abstrak: This study aims to determine whether or not there is a professional role of Islamic religious education teachers in student learning outcomes at SMP Muhammadiyah 1 Tuban for the 2023/2024 school year. This study uses quantitative research with a parametric statistical analysis approach. The research method used is pre-experiment design with one group pretest-posttest technique. The subject of this study is grade VIII students of SMP Muhammadiyah 1 Tuban with a total of 22 students. In this study, the researcher used test, interview and documentation methods as data collection techniques. The results of the study The Influence of the Professional Role of Islamic Religious Education Teachers on Student Learning Outcomes at SMP Muhammadiyah 1 Tuban for the 2023/2024 Academic Year, pretest data showed that only 6 students were declared complete with a percentage of 27% and posttest data increased with 14 students who completed with a percentage of 64%, so we can see that there was an increase in the learning outcomes of grade VIII students of SMP Muhammadiyah 1 Tuban in PAI subjects with material Debts and receivables. Based on the results of the product moment correlation test, a calculation of 0.984 was obtained so that it was included in the very strong category. And the table with the number of respondents 22 at a significant level of 0.05 is 0.4227. This shows that the calculation of > rtable (0.984 > 0.4227) can be concluded that Ho was rejected and Ha was accepted, meaning that there is an influence of the professional role of Islamic religious education teachers on the learning outcomes of grade VIII students related to the material of Debts and Receivables at SMP Muhammadiyah 1 Tuban. Based on the results of the significance test above, a tcount of 24,581 was obtained and a table with the number of respondents 22 at an average significant level of α = 0.05 dab et al = the number of respondents obtained was 1,717. So it can be concluded that tcount > ttable, then Ho is rejected and Ha is accepted. This means that the pretest and posttest data are significant. In the results of the determination test, the improvement of student learning outcomes was 96% influenced by professional teachers, while the remaining 4% was influenced by other factors that were not studied in this study.